2018
DOI: 10.3390/medicina54050080
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Direct Acting Antiviral Agents against Hepatitis C Virus Infection in Pakistan

Abstract: In Pakistan, the burden of the hepatitis C virus (HCV) infection is the second highest in the world with the development of chronic hepatitis. Interferon-based combination therapy with ribavirin was the only available treatment until a few years back, with severe side-effects and high failure rates against different genotypes of HCV. Interferon-free all-oral direct-acting antiviral agents (DAAs) approved by the FDA have revolutionized the HCV therapeutic landscape due to their efficiency in targeting different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…In the past decade, newer oral treatment regimens that act on nonstructural proteins have been introduced [7]. The use of direct-acting antiviral agents has resulted in cure rates of >90% regardless of liver fibrosis, previous treatment, or any demographic aspect [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, newer oral treatment regimens that act on nonstructural proteins have been introduced [7]. The use of direct-acting antiviral agents has resulted in cure rates of >90% regardless of liver fibrosis, previous treatment, or any demographic aspect [8].…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Due to high efficiency, low drug resistance and high safety, direct-acting antivirals (DAAs) have become the first-line treatment option for chronic HCV as recommended by international guidelines. [ 9 , 10 ] Currently, it was shown that DAAs demonstrate good safety and efficacy in patients with renal impairment infected by HCV. [ 11 , 12 ] However, reports assessing the application of DAAs in hemodialysis patients complicated with hepatitis C in Chinese real-world setting are scare.…”
Section: Introductionmentioning
confidence: 99%
“…Because the efficient direct-acting antiviral drugs against HCV now are available in Pakistan, 42 β-thalassemia patients need to be treated. However, possible new recombinants may influence on this treatment and need to be monitored.…”
Section: Discussionmentioning
confidence: 99%